How to Build an Embodiment Lab: Achieving Body Representation Illusions in Virtual Reality - Spanlang, Bernhard; Normand, Jean-Marie; Borland, David; Kilteni, Konstantina; Giannopoulos, Elias; Pomés, Ausiàs; González-Franco, Mar; Perez-Marcos, Daniel; Arroyo-Palacios, Jorge; Muncunill, Xavi Navarro; Slater, Mel (Frontiers in Robotics and AI, 2014)
Advances in computer graphics algorithms and virtual reality (VR) systems, together with the reduction in cost of associated equipment, have led scientists to consider VR as a useful tool for conducting experimental studies in fields such as neuroscience and experimental psychology. In particular virtual body ownership, where the feeling of ownership over a virtual body is elicited in the participant, has become a useful tool in the study of body representation, in cognitive neuroscience and psychology, concerned with how the brain represents the body. Although VR has been shown to be a useful tool for exploring body ownership illusions, integrating the various technologies necessary for such a system can be daunting. In this paper we discuss the technical infrastructure necessary to achieve virtual embodiment. We describe a basic VR system and how it may be used for this purpose, and then extend this system with the introduction of real-time motion capture, a simple haptics system and the integration of physiological and brain electrical activity recordings.